An Embedding 2D/3D Heterostructure Enables High‐Performance FA‐Alloyed Flexible Perovskite Solar Cells with Efficiency over 20%. Issue 22 (8th October 2021) - Wang, Zhen; Lu, Yuanlin; Xu, Zhenhua; Hu, Jinlong; Chen, Yijun; Zhang, Cuiling; Wang, Yousheng; Guo, Fei; Mai, Yaohua
Abstract: Flexible perovskite solar cells ( f ‐PSCs) have attracted increasing attention because of their enormous potential for use in consumer electronic devices. The key to achieve high device performance is to deposit pinhole‐free, uniform and defect‐less perovskite films on the rough surface of polymeric substrates. Here, a solvent engineering to tailor the crystal morphology of FA‐alloyed perovskite films prepared by one‐step blade coating is first deployed. It is found that the use of binary solvents DMF:NMP, rather than the conventional DMF:DMSO, enables to deposit dense and uniform FA‐alloyed perovskite films on both the rigid and flexible substrates. As a decisive step, an embedding 2D/3D perovskite heterostructure is in situ formed by incorporating a small amount of 4‐guanidinobutanoic acid (GBA). Accordingly, photovoltage increases up to 100 mV are realized due to the markedly suppressed nonradiative recombination, leading to high efficiencies of 21.45% and 20.16% on the rigid and flexible substrates, respectively. In parallel, improved mechanical robustness of the flexible devices is achieved due to the presence of the embedded 2D phases. The results underpin the importance of morphology control and defect passivation in delivering high‐performance flexible FA‐alloyed flexible perovskite devices. Abstract : An embedding 2D/3D heterostructure is in situ formed by incorporating a small amount of 4‐guanidinobutanoic acid, which markedly suppresses nonradiative recombination, leading to high efficiencies of 21.45% and 20.16% for the rigid and flexible perovskite devices, respectively.